Penyuluhan Modul Pengendalian Hama Tikus pada Tanaman Padi Berbasis Pengendalian Hama Terpadu di Desa Cakru Kecamatan Kencong Kabupaten Jember - Muhammad Taufiq; Ahmad Mutafakkir Alam; Agus Dharmawan; Mohamad Wawan Sujarwo (Universitas Mataram, 2026)
Rice production in Cakru Village, Kencong District, Jember Regency, is strongly supported by extensive paddy fields and the active role of farmer groups in maintaining food-crop productivity. A major constraint faced by farmers is the recurrent attack of rice field rats, particularly during the vegetative and generative stages of rice growth. This community service activity aimed to improve farmers’ knowledge and practical capacity in applying an Integrated Pest Management-based rat control module for rice cultivation. The program was implemented from September to October 2025 in partnership with Gapoktan Jaya Abadi, Cakru Village. The method consisted of initial coordination, field survey and observation, problem identification, preparation of an extension module, and participatory socialization. The module emphasized ecological rat management through habitat sanitation, synchronized planting, monitoring of active burrows, mechanical control, rational use of control inputs, and conservation of natural enemies, especially the barn owl (Tyto alba). Evaluation was conducted using observation sheets, discussion records, attendance, pre-test and post-test instruments, and participant feedback. The activity increased farmers’ understanding of rat bioecology, early detection of field infestation, and the importance of collective control at the landscape level. Farmers showed positive responses to the module because it translated technical concepts into simple field practices that could be implemented by farmer groups. The program also strengthened the role of Gapoktan as a local institution for coordinating monitoring, documentation, and follow-up actions. Sustainable implementation requires periodic mentoring, demonstration plots, development of barn owl habitat support, and integration with local agricultural extension services. This activity indicates that module-based extension can become an effective entry point for promoting environmentally sound and farmer-centered rat management in rice production areas.